Improving Conservation Outcomes with a New Paradigm for Understanding Species' Fundamental and Realized Adaptive Capacity. Issue 2 (5th August 2015) - Beever, Erik A; O'Leary, John; Mengelt, Claudia; West, Jordan M; Julius, Susan; Green, Nancy; Magness, Dawn; Petes, Laura; Stein, Bruce; Nicotra, Adrienne B; Hellmann, Jessica J; Robertson, Amanda L; et al.
Abstract: Worldwide, many species are responding to ongoing climate change with shifts in distribution, abundance, phenology, or behavior. Consequently, natural‐resource managers face increasingly urgent conservation questions related to biodiversity loss, expansion of invasive species, and deteriorating ecosystem services. We argue that our ability to address these questions is hampered by the lack of explicit consideration of species' adaptive capacity (AC). AC is the ability of a species or population to cope with climatic changes and is characterized by three fundamental components: phenotypic plasticity, dispersal ability, and genetic diversity. However, few studies simultaneously address all elements; often, AC is confused with sensitivity or omitted altogether from climate‐change vulnerability assessments. Improved understanding, consistent definition, and comprehensive evaluations of AC are needed. Using classic ecological‐niche theory as an analogy, we propose a new paradigm that considers fundamental and realized AC: the former reflects aspects inherent to species, whereas the latter denotes how extrinsic factors constrain AC to what is actually expressed or observed. Through this conceptualization, we identify ecological attributes contributing to AC, outline areas of research necessary to advance understanding of AC, and provide examples demonstrating how the inclusion of AC can better inform conservation and natural‐resource management.